Research on the reliability of the overall structure of submerged radial steel gate. - Yanchun Yu; Ziyan Zhao; Zhonghao Zhang; Weidong Chen; Yi Zhong; Yongxin An (PLoS ONE, 2025)
The safety assessment of steel gate structures holds significant social importance and economic advantages. The safety of steel gate structure is influenced by numerous random factors, so it is necessary to carry out the reliability analysis of steel gate structure. Currently, research on the reliability of steel gate structures predominantly focuses on individual components, cross-sections, or localized areas, and there are relatively few studies on the reliability of the overall structure of the steel gate. Furthermore, most of the studies only consider the role of hydrostatic pressure load, often underestimating the impact of other dynamic load combinations. Therefore, this study calculates the strength and stiffness of the overall submerged radial steel gate structure under various loading conditions, including hydrostatic pressure, hydrodynamic pressure and sediment pressure. Additionally, it conducts the analysis of the reliability regarding the overall structure of the submerged radial steel gate. The results indicate that the maximum stress and displacement values conform to the allowable limits established by relevant design codes, with the maximum stress occurring at the support hinge. The reliability analysis of the submerged radial steel gate structure was performed by considering different load combinations and material parameters as random variables, and the structure was safe at a 95% confidence level. Additionally, the sensitivity analysis of the steel gate structure was conducted, and the results showed that the hydrodynamic pressure and elastic modulus had a higher degree of influence on the results of displacement calculations, while other parameters had a relatively low degree of influence. Similarly, the hydrodynamic pressure had a greater influence on the results of stress calculations, while other parameters had a relatively small influence.